Gender differences in usage and user experience of Oiva App - Vehkanen, Laura (2015)
Previous research has indicated that gender is an important demographic to consider when designing effective and tailored technology interventions. Despite this need, gender differences is still an understudied topic in the field of technology interventions. The objective of this study was to study gender differences in usage and user experience of a mental wellness app called Oiva. Gender differences in the app’s effect on the participants’ mental well-being were also investigated. Oiva is a stand-alone mental wellness app that aims to increase its users’ psychological flexibility by teaching Acceptance and Commitment Therapy (ACT) based skills. The study population of the current study was a subset of the study population of Salwe’s Mind and Body Programme. Matched pairs design was used to study gender differences in usage and user experience of the Oiva App during a two-month mobile intervention. The study population (N = 20) consisted of 10 men (age range 33 – 55, mean 44.56, SD 7.11) and 10 women (age range 34 – 54, mean 44.43, SD 6.81). Each pair was matched on age and education, the distinguishing factor being gender. The main variables were an online questionnaire assessing usage and user experience of the Oiva App and mental wellness measurements using psychological questionnaires (PSS, RAND-36 emotional well-being, FFMQ and AAQ-II; pre = week 0, post = week 10, follow-up = week 36). In addition, objective technology usage data from the log files generated by the mobile application was investigated. The results indicate that men and women used and experienced the Oiva App and its functionalities in a similar way. There was no statistically significant gender difference in the usage data from the log files or in the online questionnaire answers regarding usage and user experience of the Oiva App. The results also suggest that the intervention had a positive effect on the participants’ mental well-being and that the effect was similar for men and women. There was a statistically significant change from pre to post intervention in PSS (psychological distress) and RAND-36 (emotional well-being) and between post and follow-up measurements in AAQ-II (psychological flexibility) but this change did not differ statistically significantly across gender. To the best of my knowledge, this is the first study to investigate gender differences in usage and user experience of a mobile mental wellness app. The results of the current study indicate that the design of the Oiva App is sufficiently gender-sensitive, as there was no gender difference in usage and user experience of the app, and the effect on mental well-being was similar across gender.